Infernal affairs 2 [videorecording (DVD)] - Liu, Weiqiang, 1960-; Liu, Weiqiang, 1960-; Mai, Zhaohui, 1965-; Mai, Zhaohui, 1965-; Zhuang, Wenqiang; Wong, Anthony, 1961-; Tsang, Eric, 1953-; Liu, Jialing, 1964-; Ng, Francis, 1961-; Chen, Guanxi, 1980-; Yu, Wenle, 1981-; Hu, Jun, 1968- (Dragon dynasty (Series), 2007)
Two men become moles on opposite sides of a war between the Hong Kong police force and the triad mob. As they perilously climb the ranks in their respective worlds, Lau and Chan enmesh themselves in a web of conflicting loyalties and deadly deceptions.